Perancangan Permanent Magnet Synchronous Generator Sultan Wind Turbine V-5 - Muhammad Irfan; Erwin Erwin; Slamet Wiyono (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
Wind is an inexhaustible source of energy so that the use of wind energy change systems will have a positive impact on the environment. Sultan Wind Turbine is a vertical axis wind turbine called the Vertical Axis Wind Turbine (VAWT). Synchronous generator is a machine that converts mechanical energy into electrical energy. Permanent magnet synchronous generator (PMSG) is a generator that uses permanent magnets to generate an air gap field instead of using an electromagnet. The purpose of this study is to design a 100 W PMSG generator for Sultan Wind Turbine using the MagNet infolytica software, then the results of looking for simulations at various speeds and various loads, after that to determine the value of the output power and efficiency at each loading and RPM. The design of this generator is the first design that is adapted to previous research where this design will optimize the simulation of previous designs that were applied to the Sultan Wind Turbine v-5. A method for designing a permanent magnet synchronous generator simulation of the sultan wind turbine which will be tested in developing its performance using the J.R. Handershot. In this design using MagNet Infolytica software to find the values ​​of Voltage and Current along with Torque obtained from simulations with the finite element method, then data processing is carried out in Excel to find the value of output power and efficiency. The results obtained in this study are by changing the geometric shape. able to produce with a rotating speed of about 100 rpm to 150 rpm at a load of 5 ohms, namely 125, 86 Watt to 231.59 Watt. The average DC voltage is 33.5 volts, the average DC current is 6.65 Ampere, the torque is 23. 24 Nm, the input power is 365.14 Watts, the output power is 231.59 Watts and the efficiency ranges from 58% to 79%.